PERAN INSENTIF PAJAK DALAM MENINGKATKAN INVESTASI HIJAU DAN PENURUNAN EMISI KARBON: STUDI EMPIRIS DI INDONESIA - Sri Yaumi; Rita Nataliawati; Mesra Berlyn Hakim; Abdul Majid (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2026)
This study aims to analyze the role of tax incentives in encouraging green investment and reducing carbon emissions in Indonesia. The study used a descriptive qualitative approach with a systematic literature review design. Secondary data sources included green fiscal policies, official government reports, and reputable journal articles related to tax incentives, green investment, and carbon emissions from 2014–2024. The study's results indicate that since the strengthening of the green fiscal framework through the 2021 HPP Law, Presidential Regulation No. 98 of 2021 concerning the Economic Value of Carbon, and various PMKs on tax incentives, the value of green investment has increased by an average of around 21% per year, particularly in the renewable energy, low-carbon manufacturing, electric vehicles, and waste management sectors. National carbon emissions showed a moderate downward trend and a cumulative reduction of approximately 9.8 million tons of CO₂e in the 2020–2023 period. These findings confirm that tax incentives play a significant role as a fiscal instrument to accelerate the transition to a low-carbon economy.